Mitochondrial transplantation: the advance to therapeutic application and molecular modulation - McCully, James D.; del Nido, Pedro J.; Emani, Sitaram M. (Frontiers in Cardiovascular Medicine, 2023)
Mitochondrial transplantation provides a novel methodology for rescue of cell viability and cell function following ischemia-reperfusion injury and applications for other pathologies are expanding. In this review we present our methods and acquired data and evidence accumulated to support the use of mitochondrial transplantation.